Oxygen transportation, electrical conductivity and electrochemical properties of layered perovskite SmBa0.5Sr0.5Co2O5+δ. (23rd February 2017) - Subardi, Adi; Chen, Ching-Cheng; Fu, Yen-Pei
Abstract: Oxygen transportation properties of SmBa0.5 Sr0.5 Co2 O5+δ (SBSC55) layered perovskite has been investigated as a potential cathode for intermediate-temperature solid oxide fuel cells (IT-SOFCs). This research includes the following items: (1) structural characteristics, thermogravimetric behavior, oxygen permeation, chemical bulk diffusion coefficient (Dchem ), and (2) the electrochemical performance of long-term testing carried out to evaluate its electrochemical stability. The D chem values for SBSC55 cathode are 2.6 × 10 −6, 9.1 × 10 −6 and 1.8 × 10 −5 cm 2 s −1 at 500 °C, 600 °C, and 700 °C, respectively. The oxygen permeation flux for SBSC55 membrane with 1.0 mm thickness increased from 0.143 mL min −1 cm −2 at 500 °C to 0.406 mL min −1 cm −2 at 800 °C under synthetic air at a flow rate of 50 mL min −1, helium at a rate of 25 mL min −1 . The activation energies of oxygen permeation for the high temperature region (700–800 °C) and low temperature region (500–650 °C) are 23.67 and 6.96 kJ mol −1, respectively. It suggested that oxygen diffusion for high temperature range is surface exchange process, low temperature range is bulk diffusion process. The long-term test of cathodic polarization resistance for SBSC55∣SDC∣SSBSC55 half-cell at 600 °C during 96 h has been carried out with an increase rate of 0.30% h −1 . Based on the impedance spectra with various oxygen partial pressure results, the rate-limiting process of ORR is determined that the oxygen ion transfer from triple-phase boundary (TPB) and/or two-phase boundary (2PB) sites of cathode is major with the minority of charger transfer reaction. Graphical abstract: Highlights: SBSC55 layered perovskite has been investigated for potential application as a cathode for solid oxide fuel cell. For long-term testing, Rp was gradually increased after 96 h testing at 600 °C with an increase rate of 0.30% h −1 . The rate-limiting process of ORR is mostly due to the transfer of the oxygen ion.